The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/14767058.2018.1517152
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of theductus venosuspulsatility index for pregnant women between 11 and 13+6weeks of gestation

Abstract: The value of DV PIV measurements is debated in the literature. Using our cohort, we defined the means and ranges of DV PIV. Determining the normal ranges of DV PIV could be helpful to anticipate congenital or chromosomal abnormalities. Further studies are needed to demonstrate the clinical importance of DV PIV, especially for patients with abnormal DV PIV measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Similar observations were noted by Baran et al [ 47 ], who reported that fetuses with developmental anomalies had an average DV-PI value of 1.22 m/s [ 47 ]. Additionally, in one of the cohort examinations regarding DV-PI reference values, it was indicated to interpret venous flow rates below 0.93 m/s and above 1.22 m/s as abnormal [ 48 ], which is compatible with our observations in this study. Likewise, the inclusion of the DV-PI parameter during ultrasound examination is a significant factor that increases the rate of heart defect diagnosis in a fetus [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were noted by Baran et al [ 47 ], who reported that fetuses with developmental anomalies had an average DV-PI value of 1.22 m/s [ 47 ]. Additionally, in one of the cohort examinations regarding DV-PI reference values, it was indicated to interpret venous flow rates below 0.93 m/s and above 1.22 m/s as abnormal [ 48 ], which is compatible with our observations in this study. Likewise, the inclusion of the DV-PI parameter during ultrasound examination is a significant factor that increases the rate of heart defect diagnosis in a fetus [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Inclusion criteria were: ( 1 ) pregnancies with optimal visualization of the DV using a wideband color Doppler technique [advanced dynamic flow (ADF)]; ( 2 ) eventual Apgar score ≥8; ( 3 ) birth weight ≥2500 grams; ( 4 ) measurements taken from a single optimal waveform after obtaining 4 to 5 consecutive uniform Doppler velocity waveforms in the tracings with 2-3 cm/s sweep speed; ( 5 ) patients with normal amniotic fluid index; and ( 6 ) patients with normal screening tests.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were: ( 1 ) gestational diabetes; ( 2 ) multiple pregnancies; ( 3 ) preeclampsia; ( 4 ) maternal cardiac rhythm disturbances; ( 5 ) maternal smoking during pregnancy; ( 6 ) polyhydramnios or oligohydramnios; ( 7 ) fetal morphological abnormality; ( 8 ) intrauterine growth restriction; ( 9 ) macrosomia; ( 10 ) fetal stillbirth; ( 11 ) eventual Apgar score <8; and ( 12 ) fetuses with transient bradycardia (deceleration).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The Pulsatility Index (PI) and Resistivity Index (RI) of the Ductus Venosus (DV) have become a common ultrasonographic measurement during pregnancy. 9 The importance of these doppler indices has been the topic of ongoing debate in the literature, and its reference value has not yet been identified in Vietnam among the normal population.…”
Section: Introductionmentioning
confidence: 99%